2020
DOI: 10.1101/2020.09.09.289900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antisense oligonucleotide therapy for SCN2A gain-of-function epilepsy

Abstract: The clinical spectrum associated with SCN2A de novo mutations (DNMs) continues to expand and includes autism spectrum disorder with or without seizures, in addition to early and late seizure onset developmental and epileptic encephalopathies (DEEs). Recent biophysical studies on SCN2A variants suggest that the majority of early seizure onset DEE DNMs cause gain of function. Gain of function in SCN2A, the principal sodium channel of excitatory pyramidal neurons, would result in heightened neuronal activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…It is important to note that healthy, wild-type animals were used in the studies presented herein. Theoretically, a disease condition could affect the activity and distribution of ASOs, but we have not observed decreased ASO activity in a variety of neurodegenerative and neurodevelopmental disease models ( 11 , 16 , 35 , 43 ). However, we recommend that each disease model should be evaluated for activity and tolerability of ASOs independently.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…It is important to note that healthy, wild-type animals were used in the studies presented herein. Theoretically, a disease condition could affect the activity and distribution of ASOs, but we have not observed decreased ASO activity in a variety of neurodegenerative and neurodevelopmental disease models ( 11 , 16 , 35 , 43 ). However, we recommend that each disease model should be evaluated for activity and tolerability of ASOs independently.…”
Section: Discussioncontrasting
confidence: 56%
“…The Malat1 ASO is the standard 5–10–5 MOE-gapmer design that is frequently used in preclinical research ( 8 , 10 , 12–14 , 16–18 ) as well as in ongoing clinical trials ( 19 , 20 ). Other studies using similar ASO chemistries have also shown broad ASO distribution in mice and NHP ( 8 , 24 , 35 ). The dose of Malat1 ASO used in NHPs herein is comparable to the doses used for human ASO drug candidates when tested in NHPs or in experimental NHP-specific compounds shown reduce target RNA ( 20 , 36 , 37 ).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Similar EEG patterns have been observed with conditional heterozygous expression of Scn2a in excitatory, but not inhibitory, neocortical neurons (Ogiwara et al, 2018). However, changes in action potential (AP) output, a feature common to many models of Na V -channelopathy-mediated epilepsy (Goff and Goldberg, 2019;Li et al, 2020;Lopez-Santiago et al, 2017;Martin et al, 2010;Tai et al, 2014), have not been observed in mature Scn2a +/À pyramidal cells (Shin et al, 2019;Spratt et al, 2019).…”
Section: Introductionmentioning
confidence: 63%
“…Similar EEG patterns have been observed in mice with conditional heterozygous expression of Scn2a in excitatory, but not inhibitory neocortical neurons (Ogiwara et al, 2018). However, changes in action potential (AP) output, a feature common to many models of Na V -channelopathy-mediated epilepsy (Goff and Goldberg, 2019; Li et al, 2020; Lopez-Santiago et al, 2017; Martin et al, 2010; Tai et al, 2014), have not been observed in mature Scn2a +/- pyramidal cells (Shin et al, 2019; Spratt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%